P49 Higher service use amongst patients with advanced COPD and psychological co-morbidities: Associations with quality of life, co-morbidities and exacerbations. (12th November 2015) - Gardener, AC; Farquhar, M; Holt Butcher, H; Moore, C; Ewing, G; White, P; Howson, S; Mahadeva, R; Booth, S; Burge, P; Mendonca, S
Abstract : Background: There is a high prevalence of anxiety and depression among people with Chronic Obstructive Pulmonary Disease (COPD). Anxiety and depression are frequently associated with increased service use, particularly hospital admission; other demographic and health variables are also known to be significant in this relationship. However, less is known about the nature of these relationships when COPD is advanced. The aim of this study was to identify the relationship between anxiety and depression and service use in patients with advanced COPD, together with the role of key demographic and health variables. Methods: A well-characterised population-based cohort of patients with advanced COPD completed the Hospital Anxiety and Depression Scale (HADS) and reported hospital and community service use and experiences. Patient demographics and health variables were also collected. Univariate analyses of associations between service use and anxiety, depression, health variables and demographics were carried out using data collected over a three month period. Results: 235 patients recruited: mean age 71.6 (SD 10.3); 61% male; mean MMRC dyspnea scale 3.68 (SD 1.040); mean CAT score 23.4 9 (SD7.5). Anxiety and depression scores (HADS) were higher than population norms. Univariate associations (Table 1 ) were identified between anxiety and contact with a GP ( p = 0 .021) and depression and in-patient admission ( p = 0 .017). Other variables crudely associated with GP service use, were the number of exacerbations managed at home ( p = 0 .006), co-morbidities ( p = 0 .014) and the CRQ dyspnea, physical and emotional domains ( p = 0 14, 0.011 and 0.032 respectively). Crude associations were also found between inpatient admissions and the number of exacerbations at home ( p = 0 .034) and the CRQ dyspnea domain ( p = 0 .014). Conclusion: Patients with advanced COPD and co-morbid anxiety were more likely to have had contact with their GP. Those with co-morbid depression were more likely to have had an in-patient admission. Variables associated with these relationships may include health related quality of life, co-morbidities and exacerbations managed at home. On-going work will validate these conclusions by analysing data collected over an 18 month period. Supportive interventions targeting patients with comorbid anxiety and depression may ameliorate the effects of psychological morbidity and reduce admissions.